2005
DOI: 10.1007/s10616-005-3759-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyzed Reduced Water Supplemented with Platinum Nanoparticles Suppresses Promotion of Two-stage Cell Transformation

Abstract: In the two-stage cell transformation theory, cancer cells first receive initiation, which is mainly caused by DNA damage, and then promotion, which enhances transformation. Murine Balb/c 3T3 cells are widely used for transformation experiments because they lose contact inhibition ability when transformed. Electrolyzed reduced water (ERW), which is produced near a cathode during electrolysis of water, is an alkaline drinking water that is beneficial to health. ERW contains a high concentration of dissolved hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…We also reported that ERW can inhibit tumor angiogenesis using human lung carcinoma A549 cells (Ye et al 2008). ERW supplemented with Pt nanoparticles has been also shown to inhibit two-stage cell transformation of Balb/c 3T3 A31-1-1 cells (Nishikawa et al 2005). Furthermore, we reported that ERW contributes to extension of the Caenorhabditis elegans lifespan, and ERW improves the symptoms of diabetes mellitus in ICR (CD-1 strain) mice (Yan et al 2010;Yan et al 2011;Li et al 2011).…”
Section: Introductionmentioning
confidence: 77%
“…We also reported that ERW can inhibit tumor angiogenesis using human lung carcinoma A549 cells (Ye et al 2008). ERW supplemented with Pt nanoparticles has been also shown to inhibit two-stage cell transformation of Balb/c 3T3 A31-1-1 cells (Nishikawa et al 2005). Furthermore, we reported that ERW contributes to extension of the Caenorhabditis elegans lifespan, and ERW improves the symptoms of diabetes mellitus in ICR (CD-1 strain) mice (Yan et al 2010;Yan et al 2011;Li et al 2011).…”
Section: Introductionmentioning
confidence: 77%
“…In the above study, although telomerase activity remained high, the telomeres became shorter with each consecutive cell division suggesting that ERAW reduced the telomere binding ability of telomerase resulting in telomere shortening [17]. Nisikawaa et al, studied the protective effect of ERAW prepared using a TI-200S electrolysis appliance (Nihon Trim Co, Osaka, Japan) on BALB/c-3T3 cells treated with 3-methyl cholantrene (initiator compound) followed by treatment with phorbol-12-myristate-13-acetate (promoter compound) [18]. They were able to establish that to inhibit the promoter, it was necessary to add PtNPs to ERAW [≈10 parts per million (ppm)] since ERAW alone strongly stimulated malignant transformation.…”
Section: Anti-cancer Effects Of Erawmentioning
confidence: 99%
“…The action of H 2 also goes beyond just elimination of excess ROS. A number of reports have shown an effect of H 2 on the regulation of gene expression, acting directly on cellular signalling pathways that are stimulated by excess ROS [18,41,42]. However, many of the reactions occurring in the presence of small quantities of H 2 still need to be elucidated [38].…”
Section: Experimental Research On Biological and Therapeutic Propertimentioning
confidence: 99%
“…A mechanism of the promotive effect of H-CM by platinum is suggested to be that the hydrogen molecules are incorporated through phagocytosis into cells in contact on the surface of platinum molecule when the hydrogen molecule is converted into atomic hydrogen by the catalytic action of platinum, the reduction activity enhances, and an ROSscavenging ability rises (18,19). Effect of a successive culture period after the treatment at 37˚C was examined by crystal violet stain assay, and elongation of culture periods from 24 h to 48 h increased the carcinostatic effect of H-CM.…”
Section: Discussionmentioning
confidence: 99%
“…However, at 42˚C an additive action of the antitumor effect is achieved in this experiment. As reasons for the increase of incorporation of hydrogen-binding platinum colloids into the cells by the heat-induced promotion of the plasma membrane permeability (19,21) and unfolding change of the nucleus made up of megasize protein-nucleic acid complexes that conduct various nuclear functions (DNA packing, repair, replication and transcription) being related to the cell killing are considered (22).…”
Section: Discussionmentioning
confidence: 99%